Pengaruh Keterlibatan Kerja, Pelatihan Kerja dan Lingkungan Kerja Terhadap Komitmen Karyawan - Saputri, Andini Bella; Fauzan, Mohammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze (1) the influence of work involvement on employee commitment; (2) the effect of job training on employee commitment and (3) the effect of the work environment on employee commitment of the Grand Candi Hotel Semarang The research sample was 110 employees of the Grand Candi Hotel Semarang. This type of research is explanatory research. Data collection uses a questionnaire using a google form, which is then sent to each respondent. Data analysis using regression with the help of SPSS software version 16. The results of the research findings show that: (1) employee involvement has a positive effect on employee commitment, (2) employee training has a positive effect on employee commitment, (3) the work environment has a positive effect on employee commitment at the Grand Candi Hotel Semarang.